SEDENTARY BEHAVIOR AT LEISURE TIME AND ITS ASSOCIATION WITH PHYSICAL ACTIVITY IN SCHOOL CONTEXT OF CHILDREN IN SOUTHERN BRAZIL - Marina Christofoletti; Giovâni Firpo Del Duca; Lays Tomazoni Gripa; Maria Alice Altenburg de Assis (Journal of Physical Education)
ABSTRACT The aim was to investigate the prevalence of sedentary behavior during leisure time and its association with demographic indicators, period and the physical activity at the school setting among children from public elementary schools in Florianópolis, SC. The instrument applied to a representative sample of schoolchildren in grades 2 through 5 was the online Web-CAAFE questionnaire, with indications of activities performed and the foods consumed on the previous day. A total of 1,831 children were investigated (8.75 years [SD±1.03]; 52.2% males), the sedentary behavior during leisure time was 56.1% (95%CI: 51.1; 61.1). There was an association between the outcome and the increase in age (seven years: PR 1.00; 8 years: PR 1.23; 9 years: PR 1.40; 10 years: PR 1.45; p<0.001) and physical inactivity during class time (PR 1.36 [95%CI: 1.21; 1.52]). The closeness to adolescence and lack of physical activity in the school environment were aspects related to the adoption of sedentary behavior.